The Employee's Right to Freedom of Religion versus the Employer's Workplace Needs: An Ongoing Battle: TDF Network Africa (Pty) Ltd v Faris 2019 40 ILJ 326 (LAC) - Ebrahim, Shamier (Potchefstroom electronic law journal, 2021)
The right to religion is well protected in the Constitution of the Republic of South Africa, 1996 (the Constitution) as well as attendant legislation. Section 15(1) of the Constitution provides that all persons have the right to freedom of religion. Section 31(1) of the Constitution then goes on to state that persons who belong to a religious community, amongst others, may not be denied the right to practise their religion with other members of that community. Section 9(3) of the Constitution prohibits the state from unfairly discriminating against any person directly or indirectly on several grounds, which include the ground of religion. Section 9(4) of the Constitution on the other hand prohibits any person from unfairly discriminating against any other person on the ground of religion, amongst others. These constitutional protections resonate in both the Labour Relations Act 66 of 1995 and the Employment Equity Act 55 of 1998. Despite these protections, the right to freedom of religion is still a contested subject in the workplace, inter alia. The contestation intensifies when the right to freedom of religion results in an employee not being able to comply with one or more of the employer's workplace needs. Employers' who do not understand the balance that has to be struck between the employee's right to freedom of religion and its workplace needs will often find themselves on the wrong side of our labour laws if they dismiss an employee without having due regard to the employee's religion. This is what transpired in TDF Network Africa (Pty) Ltd v Faris 2019 40 ILJ 326 (LAC).